PENGEMBANGAN KOMPETENSI GURU MELALUI PELATIHAN PTK DI SD NURUL HIKMAH SIDOARJO - M. Nur Rohim (Universitas Yudharta Pasuruan, 2019)
Improvement of the national education system is needed so that the quality of education increases one of the efforts to improve the quality of education is by increasing teacher professionalism. Increased professionalism of teachers is characterized by an increase in competencies that must be possessed by teachers, namely pedagogical competencies related to management of students, social competencies related to communication skills, personal competencies related to the ability of teachers to have wise personalities, and professional competencies related to ability teacher to master knowledge and improve the quality of learning. One way that can be taken in improving the quality of learning is to carry out classroom action research. Class action research is a research activity to solve learning problems. By conducting classroom action research, teachers are able to improve the learning process through a study of what is happening in their classrooms. The purpose of this training is to find out how far the teacher's knowledge and practices are about Classroom Action Research. The methods that will be used to provide this training include: lectures, questions and answers, discussions, assignments, individual guidance, and independent training in the form of projects. From the results of the overall evaluation of the implementation of the Classroom Action Research training at SD Nurul, Sidoarjo Wisdom was fairly successful, it was seen from the implementation indicators and the results obtained from this training with fairly good values.